Os saberes etnobotânicos da Comunidade Coqueiros, município de Catalão (GO) : subsídios para conservação da biodiversidade e desenvolvimento biotecnológico - Gomides, Núbia Alves Mariano Teixeira Pires (2018)
The present study was to contribute to the increase of information about the vegetation of the Cerrado by retrieving the knowledge of the Coqueiros Community, in the city of Catalão (GO), on vegetal biodiversity, recording the species, utilities and forms with the intention of subsidizing research with biotechnological research. We interviewed 36 informants, who mentioned 109 species distributed in 56 botanical families. The most representative families were: Leguminosae, Lamiaceae, Myrtacea, Annonaceae, Anacardiacea, Rutacea, Compositaea, Apocynaceae. Among the especies mentioned in this survey, 66.7% of them occur in the Cerrado as native vegetation, and 17.5% are cultivated species. For the analysis of the indications of use and forms of use, statistical indices were applied, in order to evidence the species of greater importance to the community. Thus, through the Relative Importance Index, the species Kielmeyera coriacea Mart. Was selected for studies of chemical and biological prospection, guided by the indications recorded in the interviews. Among the therapeutic indications verified by the community, and biological activities tested, it was possible to verify that the extracts and fractions of the inter-bark and leaves of K. coriacea presented antimicrobial activity, being effective in the control of diseases: oral infections; general infections; diseases of the musculoskeletal system and cutaneous tissue. The following phenolic compounds have been identified by comparison with standards: gallic acid, protocatecuic acid, epicatechin, caffeic acid, p-coumaric acid, quercetin, naringenin, luteolin, kaempferol. The ethanolic extract from K. coriacea wastes is potentially active against ulcers, since it presented a statistically significant gastric protection (88.8 and 93.5%) By means of the Consensus Value Index of Informants, it was possible to select the species Mimosa gracilis Benth., which among the medicinal categories was the one that obtained the highest value for the index. There was, therefore, a conformity in the indication of this species as antiofídica. Preliminary anti-fowl assays confirm that the extract of this species is active, inhibiting the proteolytic activity of enzymes present in the venom of Bothrops diporus and Bothrops alternatus, snakes occurring in the CenterWest of Brazil, and highly poisonous. Thus, it is observable that the ethnobotanical indications are important to guide studies of chemical and biological prospection of plant species, contributing to the biotechnological development, adding value to the native species, in order to encourage sustainable measures to conserve biodiversity.